Efektivitas Bantuan Langsung Tunai Dana Desa Bagi Masyarakat Terkena Dampak Covid-19 Dalam Perspektif Maslahah Dharuriyah (Studi Di Desa Lambhuk Kecamatan Ulee Kareng Kota Banda Aceh) - Nilam Sari; Hafidhah; M. Razi Aswanda (Fakultas Ekonomi dan Bisnis Islam, Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
The COVID-19 pandemic has had a negative social and economic impact, affecting and lowering people's living standards. This is caused by restrictions on economic activity and muamalah so that economic growth weakens, causing many people to lose their jobs which can increase the number of poverty in Indonesia. Thus, the government needs to make policies or programs to overcome these problems. This study aims to determine whether the government program in the form of Village Fund BLT in Lambhuk Village, Ulee Kareng District, Banda Aceh City has been effective and can realize maslahah dharuriyah for the community due to the COVID-19 pandemic. This study uses a qualitative descriptive method with field research data collection through interviews, documentation, and observation. The results showed that the Village Fund BLT program in Lambhuk Village can be said to be effective because it is in accordance with the rules and procedures set by the government, namely the accuracy of making choices, targeting accuracy, timeliness, and program monitoring have been felt by the community because of the goodness of the implementation of the assistance. characterized by a sense of security in terms of feelings, environment, and benefits. This assistance provides maslahah dharuriyah for the community because it can help in meeting their daily needs